Pain management during interventions in paediatric oncology in Europe – Results from a pan-European survey - Wild, Eva-Maria; Piccolo, Gianluca; Syrimi, Eleni; Kasteler, Rahel; Philips, Bob; Vassal, Gilles; Sheehan, Ciara; Kameric, Lejla; Armenkova, Theodora; Scheinemann, Katrin; Otth, Maria (EJC Pediatric Oncology, 2026)
Background: Childhood cancer survival rates have improved over the last decades. Nevertheless, childhood cancer treatment is associated with painful interventions needed for disease monitoring or treatment. It is therefore crucial to ensure appropriate pain control for painful interventions. This European survey aims to map the approaches to manage such interventions in children and adolescents with cancer. Methods: An online survey was sent to members of the European Society of Paediatric Oncology, asking the way potentially painful interventions are being managed. Interventions included lumbar puncture, bone marrow aspiration and biopsy, removal of drainages, insertion and removal of central venous lines, puncture of porth-a-cath or Ommaya reservoir, tumour biopsy, and insertion of nasogastric tube. Proposed approaches to pain management included local analgesia, systemic analgesia alone, systemic analgesia with sedation administrated by paediatric oncologists or anaesthesiologists, distraction techniques, and other methods. We further asked about drugs used and types of distraction. Results: A total of 326 health care professionals responded, representing 37 countries. The proportion of participants reporting that an intervention is performed without any pain management ranged from one participant each for bone marrow aspiration/biopsy and tumor biopsy (0,3 %), to 101 participants (31 %) for nasogastric tube insertion. The intensity of analgesia or depth of sedation per intervention is heterogeneous, so are the drugs used. Conclusion: The heterogenous results in use of analgesia or sedation during procedures indicate an unmet need. These results highlight the need for guidelines and their implementation in clinical practice. No child or adolescent undergoing cancer treatment should suffer from procedure-related pain.
CRIS-Team Scopus Importer:2025-12-26
Keywords: distraction; Paediatric oncology; pain management; sedation; supportive care